Loneliness, social anxiety, social influence and addiction that contributes to online social networking: A study among adolescent in Malaysia - Balan Rathakrishnan; Azizi Yahaya; Ismail Maakip; Peter Voo Su Kiong; Soon Singh Bikar Singh; Mohammad Rahim Kamaluddin; Mohammad Amin Wani (2018)
The present study aimed to identify the contribution of loneliness, social anxiety, social influence and addiction on online social networking. In the study 220 students from different seven schools in Johor Bahru district of Malaysia were taken as sample. The obtained data was statistically analyzed by descriptive statistics through SPSS 17 version. Results demonstrated that social influence is an influential variable and has great contribution on online social networking. Further the study also revealed that loneliness was found to be the weakest factor in online social networking.